Influence Of Policy Framework On Budgeting For Science Instructional Resources In Kenyan Secondary Schools - Odundo, Paul Amolloh; Oyier, Charles Richard (Archives of Business Research, 2017)
Instructional resources are educational inputs that aid teaching and learning process. Planning for instructional resources demands that money be set aside and budgeted for to assure their availability and adequacy. Schools financial management policy framework guides budgeting process in instructional management and the extent of involvement of science teachers.. This was a descriptive survey which targeted science teachers and principals in 6 national secondary schools, 60 county secondary schools and 66 private secondary schools in Nairobi County. Information was obtained through questionnaires and interview from a sample of 108 selected using mixture of stratified and simple random sampling techniques. Findings indicated that secondary schools in Nairobi County have a financial management policy (mean of 3.82) and that this has objectives that inform budgetary allocation for instructional resources for sciences (mean of 3.47), guide sources of funds for budgetary allocations for instructional management (Mean of 3.35), provide for standardized procedures in sourcing for science instructional resources (mean of 3.41) and has accountability provisions (Mean of 3.57). Recommendations from the study aimed at the need to institute appropriate regulatory mechanisms to enhance instructional management in terms of budgetary allocation and utilization and further research on the role science teachers in financial decision making as far as instructional management is concerned